Upaya Pemberdayaan Masyarakat Desa Bagan Melibur melalui Pengolahan Tepung Sagu menjadi Cendol Sagu Kering (CELSRING) - Hermita, Neni; Hainul Putra, Zetra; Alpusari, Mahmud; Witri, Gustimal; Astuti Mulyani, Eva; Kartika Sari, Intan; Alexander Alim, Jesi (Journal of Community Engagement Research for Sustainability, 2022)
The sago business in the Bagan Melibur Village has been around for a long time, but has not provided welfare for the community. So far, the processing of sago sandal is still in the traditional way, namely the direct drying process under the hot sun and the human-powered sago processing process, so that the production period is quite long and the results obtained are less. For this reason, this service has the aim of developing the potential of the Bagan Melibur village community in managing sago into various kinds of processed foods and beverages, one of which is a dry sago sandal (celsring). To be able to speed up the celsring processing process, it is necessary to use tools such as ultraviolet housings, so that the drying process can be carried out under any conditions. This tool can speed up the production period and production results. This community service was carried out in the Bagan Melibur Village, Merbau District, Meranti Islands Regency uses the extension method. Based on the service activities carried out, the Celsring product brand is produced which is ready to be marketed outside the Bagan Melibur area.